God is in the manger eaudiobook Reflections on advent and christmas. - Bonhoeffer, Dietrich (christianaudio, 2011)
"There are only two places where the powerful and great in this world lose their courage, tremble in the depths of their souls, and become truly afraid. These are the manger and the cross of Jesus Christ.""No priest, no theologian stood at the cradle of Bethlehem. And yet, all Christian theology finds its beginnings in the miracle of miracles, that God became human."These stirring words are among forty devotions that guide and inspire readers as they move thematically through the weeks of Advent and Christmas, from waiting and mystery to redemption, incarnation, and joy. Supplemented by an informative introduction, short excerpts from Bonhoeffer's letters, and passages from his Christmas sermons, these daily devotions are timeless and moving reminders of the true gift of Christmas.